Nanotechnology applications in urology: a review. (11th August 2014) - Maddox, Michael; Liu, James; Mandava, Sree Harsha; Callaghan, Cameron; John, Vijay; Lee, Benjamin R.
<x xml:space="preserve">Abstract</x> The objectives of this review are to discuss the current literature and summarise some of the promising areas with which nanotechnology may improve urological care. A Medline literature search was performed to elucidate all relevant studies of nanotechnology with specific attention to its application in urology. Urological applications of nanotechnology include its use in medical imaging, gene therapy, drug delivery, and photothermal ablation of tumours. In vitro and animal studies have shown initial encouraging results. Further study of nanotechnology for urological applications is warranted to bridge the gap between preclinical studies and translation into clinical practice, but nanomedicine has shown significant potential to improve urological patient care.